Abiotic Stress Tolerance in Plants: Myriad Roles of Ascorbate Peroxidase - Pandey, Saurabh; Fartyal, Dhirendra; Agarwal, Aakrati; Shukla, Tushita; James, Donald; Kaul, Tanushri; Negi, Yogesh K.; Arora, Sandeep; Reddy, Malireddy K. (Frontiers in Plant Science, 2017)
One of the most significant manifestations of environmental stress in plants is the increased production of Reactive Oxygen Species (ROS). These ROS, if allowed to accumulate unchecked, can lead to cellular toxicity. A battery of antioxidant molecules is present in plants for keeping ROS levels under check and to maintain the cellular homeostasis under stress. Ascorbate peroxidase (APX) is a key antioxidant enzyme of such scavenging systems. It catalyses the conversion of H2O2 into H2O, employing ascorbate as an electron donor. The expression of APX is differentially regulated in response to environmental stresses and during normal plant growth and development as well. Different isoforms of APX show differential response to environmental stresses, depending upon their sub-cellular localization and the presence of specific regulatory elements in the upstream regions of the respective genes. The present review delineates role of APX isoforms with respect to different types of abiotic stresses and its importance as a key antioxidant enzyme in maintaining cellular homeostasis.